Abyssocladia bruuni Levi 1964 - Vacelet, Jean (Zenodo, 2020)
Abyssocladia bruuni Lévi, 1964 (Fig 2) Material examined. Holotype DEM-241, MNHN, 36°07’S 178°32’W, 5360 m, Kermadec. 23.02.1952, Galathea, St. 661 Description . Holotype (Fig 2A) a small umbrella-shaped, dry sponge, composed of a broken stalk, 11 mm long and 0.6–1.2 mm in diameter, enlarged at the top, and with a conical cap, 7.5 mm in diameter, made of spicule fascicles inclined toward the base. Color is clear brown for the stalk, whitish for the body. The stalk is made of densely packed mycalostyles and the cap is made of radiating fascicles of mycalostyles. State of preservation: dry specimen, with numerous small debris and loose megascleres in the container. Spicules . Styles (Figs 2B, C), straight, slightly fusiform, with a very slight swelling near the head, weakly polytylote along the shaft, with a short, sharp point. 1200–1700 x 28–32 µm in the debris presumably mostly from the cap, up to 2500 x 40 µm in the stalk near the cap. Abyssochelae (Fig 2D) have a curved shaft 8 µm thick. Frontal teeth nearly in contact, always with a median longitudinal depression on the middle portion near the base. Lateral alae also nearly in contact with the opposing ones, wound at the end. 60–75 x 30–32 µm. Sigmas (Fig 2E), very numerous, with two equal ends in the same plane, relatively thick. 30–32 x 2.5–3.5 µm. Remarks . In order to preserve the holotype, which is dry and highly fragile, the spicule slides were made using the small fragments and isolated spicules that were loose in the container, as well as a small piece of the stalk near the head. The arrangement of the chelae was not observed, but they are presumably arranged along the stalk and the radiating fascicles of the cap, as in the other species of the genus with a pedunculated, disciform shape. The styles from the stalk are slightly larger than indicated in the original description. The species is remarkable for its umbrella-like shape, for the poor diversity in microscleres and for the presence of a median depression in the frontal teeth of the abyssochelae. The presence of true sigmas rather than sigmancistras is also distinctive; these sigmas were presumed to be sigmancistras by Vacelet (2006), according to the description of Lévi, but the SEM pictures confirm that they are actually sigmas. This species was recorded by Koltun, 1970 from Bougainville Trench. According to Koltun’s description and drawings, the specimen in fact differs in shape, as it is not umbrella-like but has an ovoid body, smaller microscleres, chelae that are more diverse in size and teeth and alae that are not very close as in the holotype. This identification is thus regarded as doubtful. As is typical in several other species of Abyssocladia, this species may have thick strongyles or substrongyles in its attachment base, which is not preserved. : Published as part of Vacelet, Jean, 2020, Carnivorous sponges (Porifera, Cladorhizidae) from the deep South Pacific (New Caledonia) with the description of three new species of the genus Abyssocladia and remarks on genus Cercicladia, pp. 257-276 in Zootaxa 4767 (2) on pages 259-261, DOI: 10.11646/zootaxa.4767.2.3, http://zenodo.org/record/3770819 : {"references": ["Levi, C. (1964) Spongiaires des zones bathyale, abyssale et hadale. Galathea Report, 7, 63 - 112.", "Vacelet, J. (2006) New carnivorous sponges (Porifera, Poecilosclerida) collected from manned submersibles in the deep. Pacific. Zoological Journal of the Linnean Society, 148, 553 - 584. https: // doi. org / 10.1111 / j. 1096 - 3642.2006.00234. x", "Koltun, V. M. (1970) Sponge fauna of the northwestern Pacific, from the shallows to the hadal depths. In: Bogorov, V. G. (Ed.), Fauna of the Kurile-Kamchatka Trench and its environment. Institute of Oceanology of the Academy of Sciences of the U. S. S. R., 86 Akademiya Nauk SSSR. Trudy Instituta Okeanologii in P. P. Shishov and Izdatelstvo Nauka, Moskwa, pp. 165 - 221."]}